2017
DOI: 10.1111/trf.13992
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacologic treatment and blood transfusion in fast‐track total hip and knee arthroplasty

Abstract: Preoperative treatment with SSRIs, OAs, or APs are independent risk factors for blood transfusion in elective fast-track THA and TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, our study included a relatively large sample size of patients with AS. Second, there was no information on bone mineral density or selective serotonin reuptake inhibitor utilization in the medical records, which may have also affected the results [ 15 , 40 , 41 ]. Intraoperative blood loss was estimated by the surgeon, which may have caused data inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study included a relatively large sample size of patients with AS. Second, there was no information on bone mineral density or selective serotonin reuptake inhibitor utilization in the medical records, which may have also affected the results [ 15 , 40 , 41 ]. Intraoperative blood loss was estimated by the surgeon, which may have caused data inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concluded that hip surgeries carried a higher risk of blood transfusion than did knee surgeries. 12,25 In this study, we found that patients who had hip fracture repair were more likely to be older (80 years) than those who had hip replacement (64 years). According to our multiple logistic regression, age was one of the risk factors for requiring ≥ 2 units of PRBCs transfusion (OR, 1.08; 95% CI, 1.04-1.13, P < 0.0001).…”
Section: Discussionmentioning
confidence: 63%
“…In this systematic review, data quality issues were the most commonly reported barriers, followed by the lack of data standards and limited technical capabilities. Although Denmark has a developed health data infrastructure, numerous identified projects described that data quality problems still affect health services, public health and research datasets [38, 79, 86, 98, 119, 143, 149, 151]. This is confirmed by other studies, such as a review on the Danish National Patient Registry (DNRP) where the authors concluded that data incompleteness and heterogeneous validation methods of data limited the research potential of this registry [377].…”
Section: Discussionmentioning
confidence: 87%